2022
DOI: 10.1002/ird.2753
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the performance of small‐scale irrigation schemes in subhumid Ethiopian highlands

Abstract: This study was conducted to evaluate the performance of two small-scale irrigation (SSI) schemes in the subhumid Ethiopian highlands. Water application at the farm level and flow velocity along the main canal were monitored using a Parshall flume and current meter, respectively. The infiltration was measured at the head, middle and tail of the scheme within the command area using a double-ring infiltrometer. Soil samples were collected using an auger up to 60 cm in depth. Climatic and agronomic data were suppl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 52 publications
1
3
0
Order By: Relevance
“…On the other hand, almost half of the nonuser respondents agreed positively with the contribution of irrigation in achieving household food security. This result is consistent with several empirical studies [17,26,45,52], which report the significant contribution of irrigation on improving household food security status. This indicates that, SSI plays a vital role in achieving food self-sufficiency at the household level in particular and the national level in general.…”
Section: Advances In Agriculturesupporting
confidence: 93%
See 1 more Smart Citation
“…On the other hand, almost half of the nonuser respondents agreed positively with the contribution of irrigation in achieving household food security. This result is consistent with several empirical studies [17,26,45,52], which report the significant contribution of irrigation on improving household food security status. This indicates that, SSI plays a vital role in achieving food self-sufficiency at the household level in particular and the national level in general.…”
Section: Advances In Agriculturesupporting
confidence: 93%
“…Several studies [17][18][19][20][21][22] conducted on small-scale irrigation were mainly focused on the economic implication of irrigation and most of these scholars realize the significant contribution of irrigation on farmers income and food security. On the other hand, some other studies [23][24][25][26] were focused on the technological effectiveness of SSI system. The other studies identified the challenges of SSI practice in different parts of the country [27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…The second context is peripheral areas where there are inhibited environmental conditions for agriculture and services such as lack of proper roads, market access, agricultural extensions and financial assistance. Literature affirms that economic, environmental, and technological issues [21][22][23][24][25][26], also unpredictable weather patterns, disease, lack of agricultural services, lack of capital, poor roads and lack of market access [9,[27][28][29][30][31][32] constrain the farmer sustainability, resilience and farming business performance. The third area encompasses environmental conditions and connectivity which provide potential for commercially oriented small-scale agriculture, but this potential has not yet been exploited in the rural small-scale dairy setting.…”
Section: Introductionmentioning
confidence: 99%
“…The coefficient 1.6 behind Kc was introduced to account for the inefficacy of surface irrigation due to water application losses, conveyance losses, losses for land preparation and leaching [55]. Details of surface irrigation losses in the region can be referred from Belay et al [75].…”
Section: Assessment Of Land and Water Potential For Irrigationmentioning
confidence: 99%